Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1155/2019/2782715
|View full text |Cite
|
Sign up to set email alerts
|

Development of Multidecomposition Hybrid Model for Hydrological Time Series Analysis

Abstract: Accurate prediction of hydrological processes is key for optimal allocation of water resources. In this study, two novel hybrid models are developed to improve the prediction precision of hydrological time series data based on the principal of three stages as denoising, decomposition, and decomposed component prediction and summation. The proposed architecture is applied on daily rivers inflow time series data of Indus Basin System. The performances of the proposed models are compared with traditional single-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(33 citation statements)
references
References 36 publications
(64 reference statements)
0
33
0
Order By: Relevance
“…The schematic view of proposed methodology is illustrated in Figure 1 Manuscript to be reviewed denoised daily river inflow series into multiple IMFs (Rezaie-Balf et al, a2019). The high irregular IMF is set as threshold with EBT to remove its sparsity and irregularity (Nazir et al, 2019). Further, in the prediction stage, SVM is applied on all IMFs to establish the prediction models and all predicted IMFs are aggregated to get a final prediction (Yaseen et al, a2016).…”
Section: Proposed Methodologymentioning
confidence: 99%
See 2 more Smart Citations
“…The schematic view of proposed methodology is illustrated in Figure 1 Manuscript to be reviewed denoised daily river inflow series into multiple IMFs (Rezaie-Balf et al, a2019). The high irregular IMF is set as threshold with EBT to remove its sparsity and irregularity (Nazir et al, 2019). Further, in the prediction stage, SVM is applied on all IMFs to establish the prediction models and all predicted IMFs are aggregated to get a final prediction (Yaseen et al, a2016).…”
Section: Proposed Methodologymentioning
confidence: 99%
“…In EBT method, the posterior distribution is derived with the help of prior distribution to remove sparseness and noises from the coefficients derived from wavelets (To et al, 2009;Nazir et al, 2019). In this study, we used this wavelet-based denoising method to remove noises and sparseness of VMD based coefficients.…”
Section: Ebt As a Thresholdmentioning
confidence: 99%
See 1 more Smart Citation
“…In the past few decades, reliable prediction of rivers inflow has gained popularity in all water-related departments because of their crucial role in the reservoir, irrigation management, water planning, risk evaluation and flood controlling (Porporato & Ridolfi, 2001;Jandhyala, Liu & Fotopoulos, 2009;Di, Yang & Wang, 2014;Tiwari et al, 2017;Nazir et al, 2019). Johnston & Smakhtin (2014) reviewed the importance of river data and concluded that river inflow data is an indispensable component of water resources.…”
Section: Introductionmentioning
confidence: 99%
“…Wu & Chau (2010) explained in their review that the data-driven approaches performed better than the traditional statistical models to predict the non-linear data. However, data-driven models may suffer an overfitting problem and are sensitive to parameter selection (Nazir et al, 2019). Moreover, data-driven models ignored the time-varying or multi-scale characteristics of time series data.…”
Section: Introductionmentioning
confidence: 99%